2005
DOI: 10.1007/s10562-005-7999-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Induced Oscillations of C2H4 Oxidation Over Thin Sputtered Rh Catalyst Films

Abstract: The electrochemically promoted induction of self-sustained catalytic rate and potential oscillations during C 2 H 4 oxidation was studied over sputtered Rh thin (40 nm catalyst films interfaced with ZrO 2 (8 mol% Y 2 O 3 ). The reaction rate oscillates simultaneously with the catalyst potential, and always in the opposite direction. The electrochemically induced oscillatory rate is typically 60 times larger than the open-circuit catalytic rate and 1000 times larger than the electrochemical rate of O 2) supply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…upon imposition of positive current. This TiO 2 -assisted enhanced O 2-supply to the catalyst surface is similar to that observed for Rh/TiO 2 /YSZ catalysts [34][35][36][37][38] and the underlying mechanism based on the mechanisms of SMSI and of the EPOC theory has been discussed in detail by Baranova, Foti and Comninellis [34] as outlined in Discussion. Figures 4 and 5 present steady state results of the effect of the IR-corrected potential U WR on current (open symbols) and on the catalytic rate (and corresponding conversion and TOF) for the Pt/YSZ and Pt/TiO 2 /YSZ catalysts first at T = 280°C (Fig.…”
Section: Figure 3 Compares the Transient And Steadysupporting
confidence: 73%
See 1 more Smart Citation
“…upon imposition of positive current. This TiO 2 -assisted enhanced O 2-supply to the catalyst surface is similar to that observed for Rh/TiO 2 /YSZ catalysts [34][35][36][37][38] and the underlying mechanism based on the mechanisms of SMSI and of the EPOC theory has been discussed in detail by Baranova, Foti and Comninellis [34] as outlined in Discussion. Figures 4 and 5 present steady state results of the effect of the IR-corrected potential U WR on current (open symbols) and on the catalytic rate (and corresponding conversion and TOF) for the Pt/YSZ and Pt/TiO 2 /YSZ catalysts first at T = 280°C (Fig.…”
Section: Figure 3 Compares the Transient And Steadysupporting
confidence: 73%
“…The use of titania as a dispersed thin interlayer between Rh catalyst electrodes and a solid electrolyte (YSZ) support, was first pioneered by Baranova, Foti and Comninellis for the case of Rh catalyst-electrodes [34][35][36]. These and subsequent studies [37,38] showed that the presence of the porous TiO 2 layer enhances the open-circuit catalytic rate for CH 4 and C 2 H 4 oxidation on Rh and also stabilizes the electrochemically promoted highly active Rh catalyst state. This pronounced effect was attributed to a self-driven wireless-EPOC mechanism, where O 2-promoting species are supplied from TiO 2 to Rh particles due to TiO 2 -Rh work function difference and the subsequent charge transfer from TiO 2 to Rh via a self driven EPOC O 2-transport mechanism [34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Positive polarisation causes weakening of the chemisorptive bond strength of electron acceptor adsorbates (e.g. oxygen) making easier the reduction of surface oxide to metallic rhodium [3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 99%
“…oxidation of ethylene [3][4][5][6] and propylene [7], reduction of NO with C 3 H 6 [8,9] and CO [10], that the stability of the surface rhodium oxide decreases with increasing catalyst potential. According to the phenomenon of electrochemical promotion of catalysis (EPOC) [11] or nonfaradaic electrochemical modification of catalytic activity (NEMCA effect) [12] these reactions exhibit a strong electrophobic behaviour, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon has been applied to improve the behaviour of a wide variety of catalyst in a large number of important catalytic reactions [4]. Recently the NEMCA effect has been successfully applied in environmental catalysis such as in the combustion of hydrocarbons [5][6][7][8][9][10], the oxidation of CO [11,12] and the selective reduction of NO [13][14][15][16][17]. However, apart from previous work of Marwood and Vayenas [18], there have been no further studies of electrochemical promotion on the reduction of nitrous oxide (N 2 O).…”
Section: Introductionmentioning
confidence: 99%